MYB40: fingertech B40 discount card / Hazlenah Hanafiah … [et al.] - Hanafiah, Hazlenah; Harthono, Nuur Syafiqah Syuraih Shal; Aziz, Nur Amirah Izzati; Ebun, Adelina (Faculty of Computer and Mathematical Sciences, 2023)
The Fingertech B40 discount card is designed to assist low-income students in purchasing food and materials on campus. It provides exclusive discounts on food, textbooks, stationery, and electronics, aiming to alleviate the financial burden on students while ensuring they have the necessary resources for academic success. Besides, this card is equipped with a smart card features that provide two-factors authentication. By presenting the card at participating vendors, students can take advantage of reduced prices and other benefits. This initiative promotes an inclusive learning environment by enabling economically disadvantaged students to afford essential materials. Additionally, the Fingertech B40 card supports local businesses by encouraging collaboration and sustainability within the campus community. Overall, the Fingertech B40 discount card addresses the financial challenges faced by low-income students, promotes educational equity, and enhances the student experience. Through collaboration between academic institutions, businesses, and students, this initiative fosters a more supportive and inclusive campus environment.